(untitled) - Lipschutz, Seymour (New York, 1997)
The first three chapters cover the standard material on sets, relations, and functions and algorithms. Next come chapters on logic, vectors and matrices, counting, and probability. The book than has three chapters on graph theory: graphs, directed graphs, and binary trees. Finally there are individual chapters on properties of the intergers, algebraic systems, languages and machines, ordered sets and lattices, and Boolean algebra
Keywords: algebra, abstract,combinatorial analysis,logic, symbolic and mathematical; oulines, syllabi, etc,outlines, syllabi, etc,outlines, syllabi, etc